The Influence of Career Adaptability and Work Happiness on ICT Professionals' Intention to Leave - Omar, Safiah (IGI Global, 2018)
Studies on intention to leave are important to distinguish between stayers and leavers in the organization. This article assesses whether career adaptability and work happiness can be the factors that may have influence on intention to leave among ICT professionals in Malaysia. Samples consist of 393 participants who work in ICT related companies and data were analyzed using structural equation modelling (SEM). The results indicate that individual will have lower level of intention to leave due to higher level of career adaptability and work happiness.